A survey on future networks:application scenarios and requirements analysis - Bin DAI; Yuanyuan CAO; Yijun MO (Dianxin kexue)
Faced with the severe challenges of today’s network in terms of scalability,mobility,QoS guarantee and manageability,the essential capability requirements of future networks were summarized by analyzing application scenarios of future networks,and the key functional requirements and performance indicators of future networks were proposed.Finally,the development trend of the future networks was forecasted.